2012
DOI: 10.7863/jum.2012.31.8.1169
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Duplex Sonographic Parameters Over Time After Successful Carotid Artery Stenting

Abstract: Objectives Carotid duplex sonography is the primary tool for surveillance after carotid artery stenting, but the course of sonographic velocities over time after successful stenting is unclear. The purpose of this study was to describe carotid duplex sonographic velocity parameters after successful carotid artery stenting and to determine the predictors of poststent sonographic velocities. Methods We queried institutional carotid stent and noninvasive vascular laboratory databases for internal carotid artery s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…The reason for the increased flow rates in the stent-supplied ICA appears to be, in addition to the reduction of vessel diameter after introduction of the stent, reduced arterial compliance [26,31] and altered geometry of the blood vessel [32]. Longitudinal ultrasound examinations of 82 patients with stent-supplied ICA showed that postinterventional moderately increased flow velocities in the stent (PSV 98.5 ± 21 cm/s, EDV 25.5 ± 8.1 cm/s) remained stable for more than 1 year, contradicting the idea that initial hyperperfusion after CAS causes increased flow velocities [33]. Pragmatically, an early baseline ultrasound examination is recommended in the first days after stent implantation, which can then be used for the follow-up observations in order to quantify later complications such as a hyperplasia of the neointima or formation of neoartherosclerosis.…”
Section: Videomentioning
confidence: 94%
“…The reason for the increased flow rates in the stent-supplied ICA appears to be, in addition to the reduction of vessel diameter after introduction of the stent, reduced arterial compliance [26,31] and altered geometry of the blood vessel [32]. Longitudinal ultrasound examinations of 82 patients with stent-supplied ICA showed that postinterventional moderately increased flow velocities in the stent (PSV 98.5 ± 21 cm/s, EDV 25.5 ± 8.1 cm/s) remained stable for more than 1 year, contradicting the idea that initial hyperperfusion after CAS causes increased flow velocities [33]. Pragmatically, an early baseline ultrasound examination is recommended in the first days after stent implantation, which can then be used for the follow-up observations in order to quantify later complications such as a hyperplasia of the neointima or formation of neoartherosclerosis.…”
Section: Videomentioning
confidence: 94%
“…Ursächlich für die erhöhten Flussgeschwindigkeiten in der stentversorgten ACI scheinen neben der Verringerung des Gefäßdurchmessers nach Einbringung des Stents vor allem auch eine verminderte Compliance [26,31] und eine veränderte Geometrie des Gefäßes zu sein [32]. Longitudinale Ultraschalluntersuchungen von 82 Patienten mit stentversorgter ACI zeigten, dass postinterventionell moderat erhöhte Flussgeschwindigkeiten im Stent (PSV 98,5 ± 21 cm/s, EDV 25,5 ± 8,1 cm/s) über 1 Jahr stabil blieben, was gegen eine initiale Hyperperfusion nach CAS als Ursache für die erhöhten Flussgeschwindigkeiten spricht [33]. Pragmatisch empfiehlt sich eine frühe Basis-Ultraschalluntersuchung in den ersten Tagen nach Stent-Implantation, die für die Verlaufsbeobachtungen herangezogen werden kann, um dann auch spätere Komplikationen wie eine Hyperplasie der Neointima oder die Ausbildung einer Neoartherosklerose zu quantifizieren.…”
Section: Ultraschalldiagnostik Nach Postinterventionellen Komplikationenunclassified
“…Nach einer Karotisendarteriektomie oder interventionellen Behandlung mit Dilatation und Stentimplantation in der Stenose kann der lokale Befund nach der Intervention und im weiteren Verlauf mit dem Farbduplex gut beurteilt werden (19,20) (▶Abb. 7).…”
Section: Karotisendarteriektomie Stentimplantationunclassified